Green synthesis of Fe3O4-onion peel biochar nanocomposites for adsorption of Cr(VI), methylene blue and congo red dye from aqueous solutions - Kumar Prajapati A.; Kumar Mondal M. (My University, 2025)
In the present work, Fe3O4-onion peel biochar nanocomposites (Fe3O4-OPBC NCs) were fabricated via the green method at low-temperature pyrolysis in two inert atmospheres of N2 and CO2 gas. Due to change in inert gaseous atmosphere in pyrolysis reactor, the study on surface functionality, surface area and pollutant removal ability of the synthesized nanocomposite was investigated. The green synthesized NCs in two gaseous atmospheres were characterized by BET surface area, XRD, FE-SEM, HR-TEM, FTIR, SADE pattern, XPS, and point of zero charge (pHPZC). The synthesized NCs were in-depth studied by XPS and BET analysis, and the results were matched with FTIR and FE-SEM analysis. The inert N2 atmosphere was more favorable for the higher content of oxygen-containing functional groups in the NCs but resulted in less porosity and less surface area in the NCs, whereas the CO2 treated atmosphere was more advantageous for the higher surface area and porosity, but the content of active functional groups was reduced. After the detailed characterization of both NCs, the adsorption performance of synthesized NCs was checked with Cr(VI), Methylene blue (MB) and Congo red (CR) dyes. More than 64% and 48% Cr(III) were formed after reducing Cr(VI) by Fe3O4-OPBC-1 and Fe3O4-OPBC-2 NCs at pH 2 in the solid adsorbent. Similarly, higher than 60% and 42% Cr(III) was formed after reducing Cr(VI) by the same NCs at pH 2 in residual liquid. The high reduction rate shown by Fe3O4-OPBC-1 NCs was due to the presence of oxygenated functional and polycyclic aromatic groups, which readily donate electrons. The Cr(VI), MB, and CR dye uptake investigations revealed that Freundlich multilayer chemisorption happened on the heterogeneous surface of Fe3O4-OPBC-1 and Fe3O4-OPBC-2 NCs. Both Fe3O4-OPBC-1 and Fe3O4-OPBC-2 NCs showed excellent adsorption capacity for Cr(VI), MB, and CR dye, but Fe3O4-OPBC-1 shows higher adsorption capacity, and it was 3.05% for Cr(VI), 6.91% for MB dye, and 5.84% for CR dye higher compared to Fe3O4-OPBC-2 NCs. The thermodynamic parameter estimation, co-existing anions, proposed reaction mechanism, and reusability of NCs were also investigated. © 2021 Elsevier B.V.